Disparities in chronic kidney disease burden estimates: From different sources, definitions, and equations - Yao Ma; Xiang Wang; Weihong Zhao (PLoS ONE, 2025)
Introduction The Global Burden of Disease (GBD) study provides updated epidemiological descriptions of chronic kidney disease (CKD), yet the discrepancies between its estimates and those from other sources remain unclear. Furthermore, attention is required due to the specificity of standard and computational tool for glomerular filtration rate (GFR). We aimed to evaluate CKD burden from various sources, definitions, and equations. Methods This study analyzed CKD prevalence among US adults from 1999 to 2018, using data from the GBD study 2021 and the National Health and Nutrition Examination Survey (NHANES). We calculated average prevalence and estimated annual percentage change (EAPC) for the total population and by sex. The analysis was repeated using different definitions and equations. Additionally, a literature review was conducted to extend the comparison to a global scale. Results Among US adults, the annual average estimates from the GBD and NHANES were similar, while long-term trends diverged, with disparities becoming more evident in sex-specific subgroups. Removal of racial coefficients led to an increase in the estimated CKD prevalence in Black individuals, while a decrease was observed in White individuals. The EKFC equation yielded the highest average and single-cycle CKD prevalence. Applying age-adapted thresholds reduced the prevalence of low estimated GFR (eGFR<threshold(s)) by approximately 50%, with numbers of older women reclassified into non-CKD categories. Conclusions This study highlights the differences in estimated CKD prevalence across various sources. Age-adjusted thresholds and the flexible EKFC equation hold promise for future applications in both epidemiological research and clinical practice.